2015
DOI: 10.4274/jcrpe.2011
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Hashimoto’s Thyroiditis in Children and Adolescents: a Critical Vitamin D Level for This Association?

Abstract: Objective:Vitamin D has been suggested to be active as an immunomodulator in autoimmune diseases such as Hashimoto’s thyroiditis (HT). The goal of the present study was to investigate the vitamin D status in HT patients.Methods:This prevalence case-control study was conducted on 90 patients with HT (of ages 12.32±2.87 years) and 79 age-matched healthy controls (11.85±2.28 years). Serum 25-hydroxyvitamin D3 [25(OH)D3] levels were measured in all 169 subjects.Results:The prevalence of vitamin D deficiency in HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
2
40
0
4
Order By: Relevance
“…Recently, many studies have reported associations between vitamin D deficiency and a higher incidence of autoimmune disorders in adults such as RA, SLE, psoriasis, vitiligo, MS, IBD, and Behcet disease . Also, relation of vitamin D deficiency and autoimmune diseases including type 1 diabetes mellitus, systemic lupus erythematosus, autoimmune thyroiditis, and juvenile dermatomyositis has been researched in pediatric population …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, many studies have reported associations between vitamin D deficiency and a higher incidence of autoimmune disorders in adults such as RA, SLE, psoriasis, vitiligo, MS, IBD, and Behcet disease . Also, relation of vitamin D deficiency and autoimmune diseases including type 1 diabetes mellitus, systemic lupus erythematosus, autoimmune thyroiditis, and juvenile dermatomyositis has been researched in pediatric population …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in different autoimmune diseases, vitamin D supplementation has been shown to be therapeutically effective, such as Behcet disease, RA, and SLE in adults . Studies on relationship between vitamin D deficiency and pediatric autoimmune disorders such as type 1 diabetes mellitus, systemic lupus erythematosus, thyroiditis, and juvenile dermatomyositis also revealed therapeutic effects of vitamin D supplementation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evliyaoğlu et al (23) have investigated vitamin D status in children and adolescents with CAT, and they found that CAT was observed 2.28 times more frequently in individuals with 25(OH)D3 levels <20 ng/mL. Camurdan et al (22) reported lower levels of vitamin D and higher vitamin D deficiency rates in children with Hashimoto’s thyroiditis when compared to the control group (22).…”
Section: Discussionmentioning
confidence: 99%